Peran Pembelajaran Sains Berbasis Masalah Dalam Mengasah Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Khoirunisa Khoirunisa; Putri Kesi; Yuyun Efrianefrian; Murni Murni; Astika Astika (Jurnal Sultra Elementary School, 2024)
Problem-based science learning (PBL) has an important role in honing students' critical thinking skills, especially at the elementary school level. Through problem-based learning, students are invited to be directly involved in solving problems that are relevant to everyday life, so that it can stimulate their critical thinking process. This article aims to explore various findings from literature studies related to the application of PBL in science learning in elementary schools, with a focus on developing students' critical thinking skills. The findings from this study indicate that PBL is effective in improving students' analytical, evaluation, and problem-solving skills, as well as encouraging them to think more creatively and reflectively in facing challenges.